Decentralized Rural Electrification Project in Cameroon - World Bank (Washington, DC, 2014)
Cameroon is a rural country. More than 70 percent of its people live in rural areas. In 1995, of 13,000 villages in Cameroon, only about 1,500 were connected to the national electricity grid. Most of Cameroon's 12.2 million inhabitants lack access to electricity. Only about 5 percent of all households have electricity. About 35 percent of urban households have electricity, but in rural areas this figure is less than 1 percent. Data are lacking on the number of rural clinics and schools with refrigeration and electricity or the number of villages with access to (electric) pumping facilities. The distribution of electricity in Cameroon is limited, and the growth of new subscribers is slow. New connections are only made in high load areas such as towns and industrial establishments, where grid extension is a cost-effective solution. But even in the peri-urban areas, thousands of consumers are not connected and use lead-acid batteries to run their televisions and lights. To extend the grid to rural areas would require a significant increase in investment just to keep up with population growth. Given the problems that the urban-based grid systems already experience, it is unlikely that most of the rural population and institutions, under current policies, will get electricity in the next 20-40 years.